Designing of a Rooftop Penthouse for Indoor and Outdoor Living - Naushin Fatima; Deepti Pande Rana (International Journal of Urban Design and Development, 2023)
Rooftop penthouses offer an exclusive and luxurious living experience with their stunning views and outdoor spaces. The concept of rooftop living is becoming increasingly popular, especially in urban areas where space is limited. Designing a rooftop penthouse for indoor and outdoor living refers to creating a living space on the top floor of a building that provides both indoor and outdoor living areas. The design aims to maximize the use of available space, create a comfortable living environment, and allow for easy access to outdoor spaces. The indoor living area may include bedrooms, bathrooms, a kitchen, and a study room while the outdoor living area may include a gazebo, patio, or balcony. Overall the goal of designing a rooftop penthouse for indoor and outdoor living is to create a functional, comfortable and aesthetically pleasing living space that utilizes the available rooftop space effectively. This research paper explores the critical design elements of a rooftop penthouse that combines indoor and outdoor living spaces. The paper focuses on the design of a luxury rooftop penthouse with an indoor master bedroom and an outdoor gazebo, the design of these two spaces as examples to illustrate the larger concept of designing a luxurious penthouse with seamless indoor-outdoor living. It also discusses the benefits of indoor-outdoor living, and examines the challenges of designing rooftop penthouses. The study also analyzes a case study of rooftop penthouses from around the world to identify its key features and design strategies that contribute to a successful indoor-outdoor living experience. The study will focus on specific design features, such as the use of sliding glass walls and doors, explore the use of natural elements, such as plants and water features, in enhancing the aesthetic appeal of rooftop penthouses.
Keywords: Design elements; Indoor-outdoor living; Natural Elements; Open Floor; Rooftop penthouse